Revisit the legal regime of the legal capacity of minors, based on neuroscience - CUNHA LANÇA, Hugo (Revista Jurídica Portucalense, 2023)
Because we have never subscribed to Kelsen and we disagree that the legal world can live in a dome absorbed by the contributions of other knowledge, in an intolerable legal autism, in this meager study we intend to revisit the Institute of Minority, having as a premise the teachings of neuroscience, mainly, dissecting the legal capacity of minors to act, based on their brain maturation.